Characterising the types of paediatric adverse events detected by the global trigger tool – CareTrack Kids. Issue 6 (December 2020) - Hibbert, Peter D; Runciman, William B; Carson-Stevens, Andrew; Lachman, Peter; Wheaton, Gavin; Hallahan, Andrew R; Jaffe, Adam; White, Les; Muething, Stephen; Wiles, Louise K; Molloy, Charlotte J; Deakin, Anita; et al.
Introduction: A common method of learning about adverse events (AEs) is by reviewing medical records using the global trigger tool (GTT). However, these studies generally report rates of harm. The aim of this study is to characterise paediatric AEs detected by the GTT using descriptive and qualitative approaches. Methods: Medical records of children aged 0–15 were reviewed for presence of harm using the GTT. Records from 2012–2013 were sampled from hospital inpatients, emergency departments, general practice and specialist paediatric practices in three Australian states. Nurses undertook a review of each record and if an AE was suspected a doctor performed a verification review of a summary created by the nurse. A qualitative content analysis was undertaken on the summary of verified AEs. Results: A total of 232 AEs were detected from 6, 689 records reviewed. Over four-fifths of the AEs (193/232, 83%) resulted in minor harm to the patient. Nearly half (112/232, 48%) related to medication/intravenous (IV) fluids. Of these, 83% (93/112) were adverse drug reactions. Problems with medical devices/equipment were the next most frequent with nearly two-thirds (32/51, 63%) of these related to intravenous devices. Problems associated with clinical processes/procedures comprise one in six AEs (38/232, 16%), of which diagnostic problems (12/38, 32%) and procedural complications (11/38, 29%) were the most frequent. Conclusion: Adverse drug reactions and issues with IVs are frequently identified AEs reflecting their common use in paediatrics. The qualitative approach taken in this study allowed AE types to be characterised, which is a prerequisite for developing and prioritising improvements in practice.